Advantages and disadvantages of using condoms with an intimate heterosexual partner - Planes, Montserrat; Prat, Francesc Xavier; Gómez, Ana Belén; Gras, María Eugenia; Font Mayolas, Silvia (Anales de Psicología / Annals of Psychology, 2012)
The validity and internal consistency of an anonymous self- report questionnaire assessing the perceived advantages and disadvantages of using a condom with an affective heterosexual partner was analyzed. We also analyzed the ability of the questionnaire to predict condom use in the past and the intention to use a condom within the next three months. A convenience sample consisting of 1711 college students (46.3% males, 60% aged fewer than 21) participated in the study. A cross-sectional de- sign was used. The internal consistency of the survey was comparable to similar instruments (Cronbach’s alpha of .605 for the advantages scale, .725 for the disadvantages scale). Advantages and disadvantages scores predicted systematic past condom use, although advantages were a stronger predictor. Advantages predicted the intention to use a condom in the next three months, although only among participants who were male and did not always use condoms. These findings suggest the need for prevention programs emphasizing the benefits of condom use and combating negative perceptions of their use, although emphasizing the benefits may have a greater impact on behavior.